Força e torque de radiação sobre uma partícula viscoelástica em um fluido ideal - Leão Neto, José Pereira (2015)
The study of acoustic radiation force and torque phenomena has attracted an enormous interest of the scientific community, due to applications of these phenomena in noncontact particles manipulation. In this work, we perform a theoretical analysis of acoustic radiation force and torque exerted on a homogeneous visco elastic particle in the Rayleigh scattering limit (the particle radius is much smaller than the incident wavelength) by a wave with arbitrary geometry. Our study is based on the partial-wave expansion in spherical coordinates of the incident and scattered waves. In this context, the radiation force and torque are obtained analytically in terms of an infinite series which involves the scattering and incident expansion coefficients. We assume that the particle behaves as a linear viscoelastic solid, which obeys the fractional Kelvin-Voigt model. Analytical expressions for the radiation force and torque are obtained considering the low- and high-frequency approximation in the viscoelastic model. The developed theory is used to describe the interaction of acoustic waves (traveling and standing plane waves, and zero and first-order Bessel beams) with a low-and high-density polyethylene particle. Our results show that the axial acoustic radiation force might become negative (i.e. in opposition to the wave propagation direction) when a certain condition involving the physical parameters of the particle is satisfied. Negative acoustic radiation torque due a beam of first-order Bessel may also occur when the same condition of negative radiation force is met. Remarkably, this is the first time that negative radiation force is predicted on a homogeneous particle in the Rayleigh scattering regime. Further more, the stability of the transverse acoustic radiation force generated by a Bessel beam is also investigated. We show a full 3D tractor Bessel vortex beam acting on the high-density polyethylene (HDPE). In the analysis of acoustic radiation force generated on a viscoelastic particle by a standing plane wave, relevant deviations arose in comparison with the solid elastic model for the particles. The magnitude of the radiation force and torque on a HDPE described by the viscoelastic model behaves differently (negative radiation force) compared with other materials (solid elastic and compressible fluid particle) due to traveling plane wave and Bessel beams. Finally, we believe that this study may help further enhance the development of acoustic levitation, particle handling in acoustofluids, and acoustical tweezers devices.